GEOLOGICAL AND MINERALOGICAL CHARACTERIZATION OF SOME ZEOLITIZED TUFFS FROM NWRN TRANSYLVANIA, ROMANIA - Bedelean, H.; Codrea, V.; Barbu Ο. (Bulletin of the Geological Society of Greece, 2007)
Zeolites are the most common products of transformation of silicic volcanic glass in the NW-rn part of Transylvania (Romania). Representative samples of volcanic tuffs from Mäcicas (Cluj county) were investigated by using optical (polarized light) microscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD), and wet chemical analyses. The volcanic tuffare vitreous with an acid composition. Vitreous matrix and glass shards are replaced by zeolite minerals, mainly clinoptilolite and trace amounts ofopal-CT and mordenite. X-ray diffraction semiquantitative analysis indicated that clinoptilolite represent between 60 % and 70 % of the crystalline fraction of the tuff. The clinoptilolite content of the Mäcicas tuff deposits is one of the richest in Romania. According to the present status in the zeolite market in Europe, this deposit could have industrial potential in the construction industry and in environmental applications.